2017
DOI: 10.1038/s41467-017-01229-5
|View full text |Cite|
|
Sign up to set email alerts
|

Pelagic barite precipitation at micromolar ambient sulfate

Abstract: Geochemical analyses of sedimentary barites (barium sulfates) in the geological record have yielded fundamental insights into the chemistry of the Archean environment and evolutionary origin of microbial metabolisms. However, the question of how barites were able to precipitate from a contemporary ocean that contained only trace amounts of sulfate remains controversial. Here we report dissolved and particulate multi-element and barium-isotopic data from Lake Superior that evidence pelagic barite precipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
72
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 65 publications
10
72
2
Order By: Relevance
“…Goldberg and Arrhenius () originally suggested that the accumulation rate of barium in deep‐sea sediments is a function of the rate of organic production in the euphotic zone and used BaO/TiO 2 to trace the zone of upwelling‐related enhanced productivity in the equatorial Pacific Ocean. Total Ba, as measured by the XRF core scanner, closely matches biogenic Ba in deep marine sedimentary environments, which do not contain Ba from terrigenous sources and where no significant barite remobilization occurs (Dymond et al, ; Hendy, ; Horner et al, ; Piela et al, ; Torres et al, ; Von Breymann et al, ). The dissolution resistance of biogenic barium and its strong correlation with the organic carbon (C org ) export flux additionally make Ba/Al a robust indicator of C org export flux in sediments with low clay content (Dymond et al, ; Eagle et al, ; Piela et al, ).…”
Section: Methodsmentioning
confidence: 74%
“…Goldberg and Arrhenius () originally suggested that the accumulation rate of barium in deep‐sea sediments is a function of the rate of organic production in the euphotic zone and used BaO/TiO 2 to trace the zone of upwelling‐related enhanced productivity in the equatorial Pacific Ocean. Total Ba, as measured by the XRF core scanner, closely matches biogenic Ba in deep marine sedimentary environments, which do not contain Ba from terrigenous sources and where no significant barite remobilization occurs (Dymond et al, ; Hendy, ; Horner et al, ; Piela et al, ; Torres et al, ; Von Breymann et al, ). The dissolution resistance of biogenic barium and its strong correlation with the organic carbon (C org ) export flux additionally make Ba/Al a robust indicator of C org export flux in sediments with low clay content (Dymond et al, ; Eagle et al, ; Piela et al, ).…”
Section: Methodsmentioning
confidence: 74%
“…(), Horner et al . () and Hsieh and Henderson (). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…Second, Sr-rich marine barite (>50 mol% strontium) formation (7, 9) is not thermodynamically favorable (7, 10), as the solubility of SrSO 4 (K sp,SrSO4 = 10 −6.63 ) is three orders of magnitude higher than BaSO 4 (K sp,BaSO4 = 10 −9.98 ) (3, 10). Field and laboratory studies provide evidence for the association of organics with both paradoxes (7, 11); however, the specific roles of organics in these thermodynamically unfavorable mineralization processes are not clear (7,11,12).Organic-mineral interactions play essential roles in biomineralization processes (13,14), which produce minerals with well-controlled morphologies, structures, and compositions not readily explained by traditional inorganic mineral nucleation and growth processes (13,15). Therefore, understanding how organic-mineral interactions direct mineral nucleation and growth could advance the use of biominerals as chemical archives of paleoenvironments (7,16,17).…”
mentioning
confidence: 99%
“…Field and laboratory studies provide evidence for the association of organics with both paradoxes (7, 11); however, the specific roles of organics in these thermodynamically unfavorable mineralization processes are not clear (7,11,12).Organic-mineral interactions play essential roles in biomineralization processes (13,14), which produce minerals with well-controlled morphologies, structures, and compositions not readily explained by traditional inorganic mineral nucleation and growth processes (13,15). Therefore, understanding how organic-mineral interactions direct mineral nucleation and growth could advance the use of biominerals as chemical archives of paleoenvironments (7,16,17). In addition, manipulating organic-mineral interactions offers strategies for the synthesis of crystals with tunable properties for a variety of applications (13).Despite the importance of organic-mineral interactions, the impact of the organic interface on the thermodynamics and kinetics of mineralization is poorly understood (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation